2006
DOI: 10.1002/gps.1562
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic hypotension in Parkinson's disease: association with cognitive decline?

Abstract: We conclude that there are differences in the neuropsychological performance of patients with PD and OH, supporting the hypothesis that OH might be a marker for disease progression and cognitive decline in PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 38 publications
1
84
0
1
Order By: Relevance
“…It has been identified as a risk factor for ischemic stroke (Eigenbrodt et al, 2000). As a potential indicator of underlying autonomic dysfunction that occurs with diabetes, Alzheimer's disease and dementia (Novak and Hajjar, 2010), OH may be associated with impaired cognitive performance, but these findings are inconsistent (Viramo et al, 1999,Rose et al, 2010,Allcock et al, 2006 and the link remains unclear (Novak and Hajjar, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It has been identified as a risk factor for ischemic stroke (Eigenbrodt et al, 2000). As a potential indicator of underlying autonomic dysfunction that occurs with diabetes, Alzheimer's disease and dementia (Novak and Hajjar, 2010), OH may be associated with impaired cognitive performance, but these findings are inconsistent (Viramo et al, 1999,Rose et al, 2010,Allcock et al, 2006 and the link remains unclear (Novak and Hajjar, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although studies have suggested interdependence of these manifestations, the results have been inconsistent. [11][12][13][14] Among elderly individuals, cognitive decline and other neurobehavioral signs are associated with low blood pressure, pressure fluctuations, and nondipping. [15][16][17][18][19] The hypothesis tested in this study was that neurocirculatory abnormalities may contribute to cognitive abnormalities accompanying early PD.…”
mentioning
confidence: 99%
“…Orthostatic hypotension is one of the most common symptoms of PD and it is seen with a rate of between 20-50% and it is more common in the advanced stages of the disease. In another study, no association was found between the disease severity and orthostatic hypotension 21 . While there are studies which have not found an association between autonomic dysfunction and cognitive exposure 19,22 , there are also studies which show an association between the two 23 .…”
Section: Resultsmentioning
confidence: 89%